Tracing the discursive drift from news framing to discriminatory expressions in YouTube comments - Cruz-Silva, Jorge; López-Paredes, Marco (Frontiers in Communication, 2026)
In the algorithm-mediated ecosystem, comment spaces have become arenas for discursive reinterpretation and confrontation. This study analyzes how journalistic discourse is reconfigured in these environments through the phenomenon of discursive drift, understood as the semantic and affective shift between the original framing of the news story and public responses. The case study is news videos about the Constituent Assembly in Ecuador, examined using a mixed-method approach combining text mining, lexical analysis, and semantic modeling. Over 1,600 comments from Ecuadorian media outlets were analyzed. Lexical dictionaries were constructed to detect incivility, the Hostile Environment Effect, and hate speech, and a TF-IDF model with cosine similarity was applied to measure the semantic distance between headlines and comments. The results show that 43% of the comments exhibit significant discursive drift, evidencing a systematic disconnect from the original journalistic frame. The coexistence of incivility and perceived media bias suggests that discursive drift is not a marginal phenomenon, but rather a structural condition of the digital public space, where affective polarization redefines the communicative function of journalism in contemporary democracies.